The Relationship Between Knowledge and Preventive Behaviors Toward Diabetic Foot Ulcers Among Diabetes Mellitus Patients at UPTD Pengasinan Public Health Center, Bekasi City - Afivah Sholikah, Rayssya Salwa; Pelawi, Arabta M Peraten; Simamora, Rotua Suriany (AACENDIKIA: Journal of Nursing, 2025)
The rising prevalence of diabetes mellitus as a major chronic disease poses a significant global health concern, particularly due to its potential complications such as diabetic foot ulcers. Adequate knowledge of diabetes is essential to promote effective preventive behaviors. This study aimed to examine the relationship between knowledge and preventive behaviors toward diabetic foot ulcers among diabetes mellitus patients at UPTD Pengasinan Public Health Center, Bekasi City. A descriptive analytic study with a cross-sectional design was conducted, involving 82 respondents selected from a population of 100 using Slovin’s formula. A simple random sampling technique was applied, and data were collected using a validated and reliable questionnaire. The results showed a significant relationship between knowledge level and diabetic foot ulcer prevention behavior, with a p-value of 0.000 (p < 0.05) based on the Chi-Square test. Most respondents were aged 31–45 years, predominantly female, had been living with diabetes for more than five years, held a high school education, and were mostly unemployed. Univariate analysis indicated that the majority of patients had good knowledge and fairly good preventive behaviors. These findings highlight the importance of patient education in the prevention of diabetic foot complications.